Employee Attitude Surveys: a Powerful Tool for Enhancing Organizational Effectiveness - Nakra, Rashmi (Ushus Journal of Business Management, 2005)
One of the cardinal rules of business is, "Listen to your customers". The notion that success also depends on listening to your employees is just as basic. All organizations that strive to improve performance and effectiveness are constantly faced by questions such as: 'Are our methods, working?" "Are our products and services meeting the market's expectations?" or "Why weren't we the first to launch the latest version of the product?" One of the most cost effective sources of advice is close at hand: THE WORKFORCE. Apart from asking employees as to what is working and what isn't, managements are also acutely aware of the relationship between employee satisfaction levels and customer satisfaction. This link has been validated by research studies as well as experienced by each one of us in everyday life. Most of us can vividly recall our feelings of apprehension whenever we have to visit an organization, be it a bank, a retail outlet or a restaurant where the employees look miserable and unhappy in their jobs. Each time we enter such an organization, we get an uncomfortable feeling that its employees are annoyed at us for walking in and causing them to do work.